Concrete for casting a marine wharf, concrete structure and method of construction thereof
By using a formula of silicate cement, mineral admixtures, and basalt fiber in the concrete structure of a harbor terminal, and combining it with construction methods of steel mesh layer, pad block layer, and crack-resistant mesh layer, the crack control problem of the concrete structure of the harbor terminal was solved, and the crack resistance and durability were improved.
Patent Information
- Application Number
- CN202311591043.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-24
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2043-11-24
AI Technical Summary
In existing technologies, the control of surface cracks in concrete structures at seaport terminals remains a problem, affecting construction quality.
A concrete formula containing silicate cement, mineral admixtures, and basalt fiber is adopted, and the crack resistance is improved by using a construction method of segmented pouring, setting steel mesh layer, pad block layer and crack-resistant mesh layer, combined with distributed fiber optic grating sensor monitoring.
It significantly reduces the number of cracks, improves the crack resistance and durability of concrete structures, prevents steel corrosion, monitors temperature and strain, and provides timely moisture and heat preservation curing.
Smart Images

Figure CN117658557B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of seaport terminal construction, and more particularly to a concrete for pouring seaport terminals, a concrete structure, and a construction method thereof. Background Technology
[0002] Protecting the marine ecological environment and building a maritime power have become one of the fundamental strategies for my country's marine development. Maritime transport plays a vital role in the transportation industry in my country and worldwide, leading to the rapid development of seaports and terminals. Terminals are becoming increasingly widespread along the Yangtze River and in coastal port cities, and their construction techniques are becoming more mature. However, cracks in the surface layer of cast-in-place concrete structures at terminals have always been a common quality problem in terminal construction.
[0003] Although the incorporation of steel or polyethylene fibers into surface concrete is now common and has played a positive role in crack control, crack control remains a frequent issue. Analyzing the causes of cracks and implementing effective crack control measures are crucial for controlling cracks in wharf surface concrete and have significant guiding implications for future wharf surface concrete crack prevention and control.
[0004] Therefore, how to provide concrete, concrete structure and preparation method for pouring seaport wharves, so as to improve the crack resistance of concrete structures used to construct seaport wharves, is the technical problem that this invention urgently needs to solve. Summary of the Invention
[0005] In view of the shortcomings or deficiencies of the prior art, the technical problem to be solved by the present invention is to provide a concrete for pouring seaport wharves, a concrete structure and a construction method thereof, which can improve the crack resistance of the concrete structure used to construct seaport wharves.
[0006] To solve the above-mentioned technical problems, the present invention provides a concrete for pouring seaport wharves, comprising:
[0007] 380-420 parts of cementitious material;
[0008] 730-770 parts of sand;
[0009] 3-5 parts water-reducing agent;
[0010] 1060-1100 parts of crushed stone;
[0011] Add 140-150 parts of water;
[0012] The cementitious material includes at least: a gel substrate composed of silicate cement; 20-30% mineral admixtures; and 2-4% basalt fiber.
[0013] Further, as a preferred embodiment, the basalt fiber is a short-cut fiber; the length of the basalt fiber is 10-20 mm; the diameter of the basalt fiber is 0.3-0.5 mm; the tensile strength of the basalt fiber is ≥800 MPa; and the elastic modulus of the basalt fiber is ≥45 GPa.
[0014] Further, as a preferred embodiment, the mineral admixture includes: mineral powder and fly ash.
[0015] Further, as a preferred embodiment, the weight ratio of the mixed water to the weight of the cementitious material is 0.34 to 0.38.
[0016] Further, as a preferred embodiment, the unit weight of the cementitious material is 400 kg / m³. 3 .
[0017] This application also provides a construction method for concrete structures used in seaport wharves, comprising the following steps:
[0018] Prepare the concrete used for pouring the seaport wharf.
[0019] After setting expansion joints and pouring the concrete in sections in the area to be constructed, a concrete base layer is formed.
[0020] A steel mesh layer is laid on the concrete base layer;
[0021] Spacers are spaced on the steel mesh layer;
[0022] A crack-resistant mesh layer is provided on the pad;
[0023] The concrete is used to fill and pour the steel mesh layer, the pad block layer, and the crack-resistant mesh layer, as well as the filling space formed between them, to form a concrete structure.
[0024] Furthermore, as a preferred embodiment, in the segmented casting, the width of each segment is 5m to 10m, and the length of each segment is 50m to 100m.
[0025] Further, as a preferred embodiment, the mesh spacing of the steel mesh layer is 100mm to 150mm.
[0026] Further, as a preferred embodiment, the steel mesh layer comprises: a plurality of steel bars distributed in a mesh pattern; wherein the diameter of the steel bars is 8 to 10 mm.
[0027] Furthermore, preferably, both the pad layer and the crack-resistant mesh layer are made of basalt fiber with a density of 2 g / cm³. 3 ; and / or the pad layer includes: a plurality of pad components spaced circumferentially along the concrete base layer.
[0028] Further, as a preferred embodiment, the thickness of the crack-resistant mesh layer is set to 1-3 mm; the mesh size of the crack-resistant mesh layer is 5-10 cm; and / or the height of the pad layer is 3-5 cm.
[0029] Further, as a preferred embodiment, after the steel mesh layer, the pad block layer, and the crack-resistant mesh layer are cast and shaped by the filling material, the thickness of the protective layer covering the crack-resistant mesh layer is 20-30 mm.
[0030] Further, as a preferred embodiment, the strength grade of the concrete is C40 to C50.
[0031] Further, preferably, the method further includes the following steps before filling and pouring the concrete into the reinforcing mesh layer, the spacer layer, and the crack-resistant mesh layer, as well as the filling spaces formed between them, to form the concrete structure:
[0032] Through holes are provided on the pad layer for forming the binding connection;
[0033] The crack-resistant mesh layer, the pad block layer, and the steel mesh layer are tied together.
[0034] Furthermore, preferably, the step of setting the crack-resistant mesh layer on the pad layer includes the following steps before or after the step of setting the crack-resistant mesh layer on the pad layer:
[0035] Fiber Bragg grating sensors are respectively installed on the inner and outer sides of the steel mesh layer; wherein, the fiber Bragg grating sensors are used for communication connection with an external monitoring system; the fiber Bragg grating sensors include at least: temperature and strain sensors.
[0036] This application also provides a concrete structure, which is constructed using the above-described construction method for concrete structures used in seaport terminals.
[0037] Compared with existing technologies, this application can improve the crack resistance of concrete structures.
[0038] Furthermore, the concrete structure and construction method provided by this invention have been verified through experiments to have a good crack control effect, significantly reducing the number of cracks by 80%.
[0039] The concrete structure provided by this invention improves the overall durability of the structure by incorporating basalt fiber materials, replacing the original ultra-high performance concrete and the use of internal steel mesh, thereby minimizing or slowing down corrosion in marine environments.
[0040] Furthermore, the design of embedding distributed optical fibers inside the basalt fiber mesh and basalt fiber reinforcement in the concrete structure provided by this invention can effectively monitor the temperature and strain at the point of surface constraint concentration, so that staff can take appropriate measures such as moisture retention and heat preservation based on the information monitored by the monitoring system. Attached Figure Description
[0041] Other features, objects, and advantages of this application will become more apparent from the following detailed description of non-limiting embodiments with reference to the accompanying drawings:
[0042] Figure 1 The eighth embodiment of the present invention is a flowchart of the construction method for a concrete structure for a seaport terminal.
[0043] Figure 2 : A schematic diagram of the concrete structure for a seaport terminal in the eighth embodiment of the present invention;
[0044] Figure 3 The flowchart of a preferred construction method for a concrete structure for a seaport terminal in the eighth embodiment of the present invention is shown.
[0045] Attached reference numerals: 1. Concrete base layer; 3. Steel mesh layer; 2. Pad layer; 4. Crack-resistant mesh layer. Detailed Implementation
[0046] The following will further explain the concept, specific structure, and technical effects of the present invention in conjunction with the accompanying drawings, so as to fully understand the purpose, features, and effects of the present invention.
[0047] Example 1
[0048] This embodiment provides a type of concrete for pouring seaport wharves, comprising the following components:
[0049] 320 parts of cementitious material;
[0050] 751 portions of sand;
[0051] 4 parts water-reducing agent;
[0052] 1080 portions of crushed stone;
[0053] 151 parts of water were added.
[0054] The aforementioned cementitious material includes at least: a gel matrix composed of silicate cement; and basalt fibers composed of mineral admixtures and chopped fibers. The mineral admixtures include: mineral powder and fly ash. The silicate cement is ordinary silicate cement with a grade of P.O42.5.
[0055] Furthermore, the above components are proportioned according to the proportioning parameters shown in Table 1 below and concrete is produced.
[0056] Specifically, in this embodiment, the length of the basalt fiber is 10-20 mm; the diameter of the basalt fiber is 0.3-0.5 mm; the tensile strength of the basalt fiber is ≥800 MPa; and the elastic modulus of the basalt fiber is ≥45 GPa.
[0057] Further, as a preferred embodiment, the weight ratio of the mixed water to the weight of the cementitious material is 0.36.
[0058] Furthermore, as a preferred embodiment, the unit weight of the above-mentioned cementitious material is 400 kg / m³. 3 .
[0059] Furthermore, preferably, the water-reducing agent is a polycarboxylate water-reducing agent.
[0060] Furthermore, as a preferred embodiment, the crushed stone in this embodiment is mainly composed of three types of graded stones with different coarseness and proportions, such as: first-graded stone, second-graded stone, and third-graded stone. The diameter of the first-graded stone is 10-20 mm, the diameter of the second-graded stone is 20-35 mm, and the diameter of the third-graded stone is 35-50 mm. The proportions of the first-graded stone, second-graded stone, and third-graded stone are 5:3:2. This combination of different grades of crushed stone and their proportions helps to adjust the bulk density of the aggregate, thereby improving the internal density and strength of the concrete.
[0061] Additionally, it is worth mentioning that the fly ash in this embodiment is Class I fly ash. The mineral powder is preferably S95 grade mineral powder.
[0062] The sand used in this embodiment is river sand with a fineness modulus of 1.6 to 3.7.
[0063] Table 1 shows the mix proportions of the concrete used for pouring the harbor wharf in this embodiment.
[0064]
[0065] Relevant experimental data show that concrete prepared with the above proportions for pouring harbor wharves exhibits better crack resistance, lower shrinkage, and durability compared to concrete with ordinary compositions in high-humidity environments, such as harbor environments.
[0066] Example 2
[0067] This embodiment provides a concrete for pouring seaport wharves. This embodiment is largely the same as Embodiment 2, except that the cement in the cementitious material is 268 parts; fly ash is 40 parts; mineral powder is 80 parts; and basalt fiber is 12 parts.
[0068] Table 2 shows the mix proportions of the concrete used for pouring the harbor wharf in this second embodiment.
[0069]
[0070] Example 3
[0071] This embodiment provides a concrete for pouring seaport wharves. This embodiment is largely the same as Embodiment 2, except that the cement in the cementitious material is 264 parts and the basalt fiber is 16 parts.
[0072] Table 3 shows the mix proportions of the concrete used for pouring the harbor wharf in Example 3 of this embodiment.
[0073]
[0074] Comparative Example 1
[0075] This comparative example provides concrete for pouring seaport wharves. This comparative example is largely the same as Example 1, except that the cement in the cementitious material is 384 parts; the basalt fiber is 16 parts; and the mineral admixture is 0 parts.
[0076] Table 4 shows the mix proportions of the concrete used for pouring the harbor wharf in Comparative Example 1.
[0077]
[0078] Comparative Example 2
[0079] This embodiment provides a concrete for pouring seaport wharves. This embodiment is largely the same as Embodiment 2, except that the cement in the cementitious material is 280 parts and the basalt fiber is 0 parts.
[0080] Table 5 shows the mix proportions of the concrete used for pouring the harbor wharf in Comparative Example 2.
[0081]
[0082] Comparative Example 3
[0083] This comparative example provides concrete for pouring seaport wharves. This comparative example is largely the same as Example 1, except that the cement in the cementitious material is 320 parts; fly ash is 20 parts; mineral powder is 60 parts; and basalt fiber is 0.
[0084] Table 6 shows the mix proportions of the concrete used for pouring the harbor wharf in Comparative Example 3.
[0085]
[0086] Comparative Example 4
[0087] This comparative example provides concrete for pouring seaport wharves. This comparative example is largely the same as Example 2, except that the cement in the cementitious material is 260 parts and the basalt fiber is 20 parts.
[0088] Table 7 shows the mix proportions of the concrete used for pouring the harbor wharf in Comparative Example 4.
[0089]
[0090] Comparative Example 5
[0091] This comparative example provides concrete for pouring seaport wharves. This comparative example is largely the same as Example 2, except that the cement in the cementitious material is 250 parts and the basalt fiber is 30 parts.
[0092] Table 8 shows the mix proportions of the concrete used for pouring the harbor wharf in Comparative Example 5.
[0093]
[0094] Experimental data analysis
[0095] Experimental methods:
[0096] The autogenous shrinkage performance index of concrete is based on GB / T 50081—2002 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete Mixtures";
[0097] The test index for thermal insulation temperature rise of concrete refers to DL / T 5150—2001 "Test Procedure for Hydraulic Concrete";
[0098] The electrical flux test parameters refer to GB / T 50082 "Standard for Test Methods of Long-Term Performance and Durability of Ordinary Concrete";
[0099] The compressive strength performance indicators refer to GB / T 50107-2010 "Standard for Testing and Evaluation of Concrete Strength".
[0100] Table 9 shows the performance parameters of the concrete prepared in each embodiment.
[0101]
[0102]
[0103] As shown in the table above, this embodiment effectively reduces autogenous shrinkage by adding mineral admixtures and basalt fibers to the cementitious material and mixing them according to a preset ratio. The synergistic effect of the mineral admixtures and basalt fibers (composed of short-cut fibers) also ensures good crack resistance and flexural strength. Specifically, by adding fly ash and mineral powder, the embodiment reduces cement usage and hydration heat, thereby lowering the temperature rise and reducing temperature cracks caused by excessive temperature differences. Especially when combined with a water-reducing agent to suppress the shrinkage effect of concrete during hydration, it reduces the tensile stress under strong bottom constraint during shrinkage, significantly reducing the risk of cracking. Furthermore, since mineral powder has better durability than fly ash, increasing the amount of mineral powder increases the durability of concrete, but also increases shrinkage. Therefore, by further incorporating basalt fiber to replace part of the mineral powder to bear the stress generated by shrinkage during concrete casting, early-stage internal cracks and pores in the concrete can be suppressed. Maintaining a suitable basalt fiber ratio, such as 2-4%, and controlling the ratio of fly ash to mineral powder within a suitable range, such as less than 1:2, can effectively reduce cement usage, hydration heat release, and temperature rise. This allows for a significant increase in the compressive strength and durability indicators of concrete (referring to autogenous shrinkage and electrical flux, whose values are inversely proportional to durability indicators) while avoiding excessive temperature differences, effectively reducing manufacturing costs. Moreover, comparative studies show that as the proportion of cement in the cementitious materials of concrete decreases, its compressive strength gradually decreases, while autogenous shrinkage and electrical flux gradually increase, meaning that durability indicators gradually decrease.
[0104] Example 8
[0105] like Figure 1 and Figure 2 As shown in the figure, this embodiment provides a construction method for a concrete structure used in a seaport terminal, which includes the following steps:
[0106] Step S10: Prepare the concrete for pouring a seaport wharf provided in any one of the above embodiments 1 to 3;
[0107] Step S20: After setting expansion joints 11 on the area to be constructed (not shown in the figure), such as the foundation pile foundation of a harbor wharf, the concrete is poured in sections to form a concrete base layer 1;
[0108] Step S30: Lay a steel mesh layer 3 on the concrete base layer;
[0109] Step S40: Spacer blocks 2 are provided at intervals on the steel mesh layer;
[0110] Step S50: Set a crack-resistant mesh layer 4 on the pad layer;
[0111] Step S60: Fill and pour the concrete into the steel mesh layer, the pad block layer, and the crack-resistant mesh layer, as well as the filling space formed between them, to form a concrete structure.
[0112] The high-performance concrete structure produced through the above steps maintains a predetermined distance between the crack-resistant mesh layer 4 and the concrete base layer 1. Furthermore, a steel mesh layer 3 and a spacer layer 2 are filled between the concrete base layer 1 and the crack-resistant mesh layer 4. This ensures that even if surface cracks, such as microcracks, appear during or after the pouring of concrete with good crack resistance and durability to form the surface layer, the spacer layer 2 prevents the steel mesh layer 3 from being exposed to the outside through microcracks and becoming susceptible to corrosion. This effectively prevents corrosion of the internal steel reinforcement, especially in high-humidity environments such as those found in harbor terminals, thus significantly improving the crack resistance of the concrete structure. In addition, by using concrete with added water-reducing agents, the shrinkage effect generated during hydration can be effectively suppressed, reducing the tensile stress under strong bottom constraint during shrinkage and greatly reducing the risk of cracking. Moreover, the steel mesh layer prevents excessive internal stress generated by internal shrinkage from causing cracks, while simultaneously improving the flexural and compressive strength of the concrete structure.
[0113] In addition, it is worth mentioning that the area to be constructed in this embodiment is the surface layer of the harbor terminal. For example, in this embodiment, the panel is a prefabricated panel with a height of 150mm, a width of 34m, and a length of 593m.
[0114] Furthermore, as a preferred embodiment, in the segmented casting, the width of each segment is 5m to 10m, and the length of each segment is 50m to 100m. The aforementioned expansion joints can be formed by setting corresponding templates before casting.
[0115] Furthermore, as a preferred embodiment, the mesh spacing of the aforementioned steel mesh layer 3 is 100mm to 150mm. This mesh spacing arrangement not only protects the concrete base layer 1 but also effectively prevents excessive internal stress caused by internal shrinkage of the concrete, thus improving its overall crack resistance and flexural strength.
[0116] Further, as a preferred embodiment, the above-mentioned steel mesh layer 3 includes: a plurality of steel bars distributed in a mesh pattern; wherein the diameter of the steel bars is 8 to 10 mm.
[0117] Furthermore, preferably, both the pad layer 2 and the crack-resistant mesh layer 4 are made of basalt fiber with a density of 2 g / cm³. 3The basalt fiber pad layer 2 and the crack-resistant mesh layer 4 not only consolidate the concrete, but also effectively slow down the corrosion of internal steel bars by some chloride ions and fumes, extend the service life of the structure, and further improve the crack resistance of the concrete structure.
[0118] Furthermore, as a preferred embodiment, the aforementioned crack-resistant mesh layer is prefabricated as a single unit according to design requirements.
[0119] Furthermore, as a preferred embodiment, the aforementioned pad layer 2 includes: a plurality of pad components spaced circumferentially along the concrete base layer 1.
[0120] Further, as a preferred embodiment, the thickness of the aforementioned crack-resistant mesh layer 4 is set to 1–3 mm; the mesh size of the crack-resistant mesh layer 4 is 5–10 cm. This structure not only facilitates rapid penetration of the concrete base layer during subsequent concrete pouring to achieve integral casting, but also effectively slows down the corrosion of internal reinforcing steel by some chloride ions and fumes, thereby extending the structural lifespan and further improving the crack resistance of the surface concrete structure.
[0121] Furthermore, as a preferred embodiment, the thickness of the aforementioned pad layer 2 is 3 to 5 cm.
[0122] Furthermore, as a preferred embodiment, after the aforementioned steel mesh layer 3, the pad block layer 2, and the crack-resistant mesh layer 4 are cast and molded, the thickness of the protective layer covering the crack-resistant mesh layer 4 is 20-30 mm. By setting these structural parameters, cracks or crack expansion caused by internal stress in the concrete can be effectively avoided, thereby improving the overall flexural and crack resistance.
[0123] Further, as a preferred embodiment, the aforementioned pad layer 2 includes: a plurality of pad components spaced circumferentially along the concrete base layer 1, such as... Figure 2 The pad component 2a and pad component 2b are shown.
[0124] Furthermore, as a preferred embodiment, the aforementioned crack-resistant mesh layer 4, pad block layer 2, and reinforcing mesh layer 3 are bound together. Each of the aforementioned pad block components also has through holes 21 for forming the binding connection.
[0125] Further, as a preferred option, such as Figure 3 As shown, the step of setting the crack-resistant mesh layer 4 on the above-mentioned pad layer 2, that is, before or after step S50, also includes the following steps:
[0126] Step S45: Fiber Bragg grating sensors are respectively installed on the inner and outer sides of the above-mentioned steel mesh layer 3; wherein, the fiber Bragg grating sensors are used for communication connection with an external monitoring system; the fiber Bragg grating sensors include at least: temperature and strain sensors.
[0127] By pre-installing temperature and strain sensors inside the concrete and electrically connecting them to an external monitoring system, it is possible to collect temperature and strain data inside the concrete. This allows for effective summarization of temperature and strain at the center and surface of the structure, enabling timely maintenance measures to be taken.
[0128] Further, as a preferred embodiment, the reinforcing mesh layer 3 is composed of a plurality of reinforcing bars 3a arranged in a grid pattern, wherein two reinforcing bars 3a stacked and connected vertically are tied together. Furthermore, the reinforcing mesh layer 3 also includes a plurality of basalt reinforcement bars 3b arranged parallel to each other between adjacent reinforcing bars 3a, wherein each basalt reinforcement bar 3b has a hollow cavity, and a temperature sensor and / or strain sensor is disposed within the hollow cavity. It should be noted that the reinforcing mesh layer 3 in this embodiment can be composed of a single layer of reinforcing mesh or multiple layers of reinforcing mesh stacked sequentially; specific limitations and descriptions will not be elaborated further here.
[0129] Furthermore, as a preferred embodiment, each basalt reinforcement 3b is equidistantly distributed on the steel mesh layer 3 to enable stress detection and temperature detection in different areas.
[0130] In addition, as a preferred embodiment, some basalt reinforcement 3b is located below the pad block member 2b, and some is located below the non-pad block member, so as to facilitate zoned detection of the area where the pad block member is located and the area where the non-pad block member is located, and to compare the differences, thereby improving the accuracy of stress detection and / or temperature detection, and facilitating subsequent maintenance and repair.
[0131] Example 9
[0132] This embodiment provides a concrete structure for a seaport terminal, which is prepared using the construction method for a concrete structure for a seaport terminal provided in Embodiment 8 above.
[0133] The above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. The present invention has been described in detail with reference to preferred embodiments. Those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the present invention, and all such modifications and substitutions should be covered within the scope of the claims of the present invention.
Claims
1. A construction method for concrete structures used in seaport wharves, characterized in that, Includes the following steps: The concrete is prepared from the following components by weight: 380-420 parts cementitious material, 730-770 parts sand, 3-5 parts water-reducing agent, 1060-1100 parts crushed stone, and 151 parts water. The cementitious material comprises silicate cement, mineral admixtures, and basalt fiber, with the mineral admixtures accounting for 20%-30% of the total weight of the cementitious material and the basalt fiber accounting for 2%-4% of the total weight of the cementitious material. The mineral admixtures consist of mineral powder and fly ash. The crushed stone is composed of a first-grade aggregate, a second-grade aggregate, and a third-grade aggregate mixed in a weight ratio of 5:3:2, with the first-grade aggregate having a diameter of 10-20 mm, the second-grade aggregate having a diameter of 20-35 mm, and the third-grade aggregate having a diameter of 35-50 mm. After setting expansion joints and pouring the concrete in sections in the area to be constructed, a concrete base layer is formed, wherein the width of each section is 5m to 10m and the length is 50m to 100m. A steel mesh layer is laid on the concrete base layer. The mesh spacing of the steel mesh layer is 100mm to 150mm. The steel mesh layer includes a plurality of steel bars distributed in a mesh pattern. The diameter of the steel bars is 8 to 10mm. Spacer blocks are spaced on the steel mesh layer. The spacer blocks are made of basalt fiber with a density of 2 g / cm³ and a height of 3 to 5 cm. A crack-resistant mesh layer is provided on the pad block layer. The crack-resistant mesh layer is made of basalt fiber and has a thickness of 1-3 mm and a mesh size of 5-10 cm. The concrete is used to fill and pour the steel mesh layer, the pad block layer, and the crack-resistant mesh layer, as well as the filling space formed between them, so that the protective layer covering the crack-resistant mesh layer after pouring is 20-30mm thick, to form a concrete structure. Specifically, through holes are provided on the pad block layer for forming a binding connection; the crack-resistant mesh layer, the pad block layer, and the reinforcing mesh layer are bound together; and fiber optic grating sensors are respectively provided on the inner and outer sides of the reinforcing mesh layer. The fiber optic grating sensors include at least a temperature sensor and a strain sensor for communication connection with an external monitoring system.
2. A concrete structure, characterized in that, The concrete structure for a seaport terminal is constructed using the method described in claim 1.
Citation Information
Patent Citations
Anti-cracking / corrosion-resistant concrete and preparation method and application thereof, concrete pressure pipe and preparation method thereof
CN109320167A
Prevent concrete cracking's wall structure
CN208396086U
